Development of a proposed framework for Tahkim in the Malaysian construction industry - Arifin, Muhammad Arifuddin; Abdul Rashid, Khairuddin; Ahmad Sarkawi, Azila; Hasan, Sharina Farihah (2015)
This study examines the current practice of arbitration in the construction industry and Tahkīm in Sharī’ah in order to explore the opportunity of employing the latter in the Malaysian construction setting. The scope of the study is to identify the appropriate framework in doing so by describing the key processes and procedures including the criteria of dispute, the matters related to Hakam i.e. the appointment and his characteristics, the setting of Tahkīm session and the award of Tahkīm. The methodology employed comprises of literature review, and two-tiered semi-structured interviews. Experts in the area of construction contract, law, Sharī’ah law, Fiqh and Usul Al-Fiqh are the key references for the study. The findings of this study suggest that there is an opportunity to employ Tahkīm in resolving the construction disputes in Malaysia, and the framework that contains the key processes and procedures aforementioned has been proposed. The outcome of the study is considered significant in terms of the contribution to the concept of alternative dispute resolution (ADR) whereby a new option has been proposed to resolve construction disputes in this country; apart from enhancing the understanding of Islamic law related to commercial disputes that can be applied in terms of construction industry.